METODE PEMBELAJARAN AKIDAH AKHLAK DALAM UPAYA MENUMBUHKEMBANGKAN SIKAP MODERAT DI MI ISLAMIYAH MOJOKERTO - Munawaroh, Erika; Rahmat, Rahmat (ANDRAGOGI, 2022)
Modern life is marked by the development of technology and science, and along with this development the task of educators, especially moral educators in madrasas, is demanded to be more innovative so that students can easily accept it. This study aims to analyze the learning methods that can be utilized in learning akidah akhlak and to analyze the implications of these methods for developing a moderate attitude. Type of Research This is a qualitative research with a case study approach. The research location was carried out at MI Islamiyah, the data collection techniques were participant observation, in-depth interviews and documentation, while the data analysis technique began with data reduction, data presentation, data verification, while the technique of testing the validity of the data was by means of: credibility, transferability, dependability, confirmability. The results showed that the learning method for akidah akhlak at MI Islamiyah consisted of 9 methods, namely: 1) exemplary method, 2) custom and habit method, 3) advice method, 4) pilot method, 5) motivational method, 6) story method, 7 ) Lecture method, 8) Question and answer method, 9) Discussion method. As well as the nine learning methods of the moral creed have implications for developing the moderate attitude of the participants. This can be seen in the attitudes of students such as, 1) Students carry out vertical worship (spirituality), 2) Students carry out horizontal (social) worship.